Political campaigns on social media - margins of legal personal data collection and use of data under the GDPR - Zitāns, Dairis (Riga Graduate School of Law, 2021)
The world is experiencing levels of information flows like never before and with the development of digital technologies and online services, the importance to secure, protect and limit this flow is as important as ever. In 2016, the European Union took a big step forward in the field of data protection and adopted the new General Data Protection Regulation which meant a more secure digital environment for users online and headaches for app developers in terms of how to comply with this regulation. Nevertheless, questions about the use of private data on social media platforms for political campaigning during the 2016 US Presidential Elections and the UK’s Brexit referendum attracted even bigger attention to how GDPR will be able to regulate these processes. The Author attempts to explain to what extent the GDPR regulates political campaigning on social media using interpretation of law together with practical issues before reaching the conclusion that the GDPR should be more specific towards questions that are left for interpretation and more general towards questions related to technical requirements
Keywords: Data protection; Political campaigns